PENGARUH PENERAPAN METODE ABC (ANTICIPATION, BUILDING KNOWLEDGE, AND CONSOLIDATION) BERBANTUAN FITUR NEARPOD TERHADAP PENGUATAN REGULASI DIRI PESERTA DIDIK DI SDN 159 PALEMBANG - Repi Ayu Anggita; Aquami; Middya Botty (STKIP Subang, 2026)
This study was motivated by the low level of self-regulation among second-grade students at SDN 159 Palembang in mathematics learning, characterized by easily distracted behavior, lack of independence, and high dependency on teacher instructions. This study aimed to examine the effect of the ABC method (Anticipation, Building Knowledge, and Consolidation) assisted by Nearpod on strengthening students' self-regulation. A quantitative approach was employed using a true-experimental design with a Posttest-Only Control Group Design. The sample consisted of 50 students, comprising 26 students in the experimental class (II.A) and 24 students in the control class (II.B), selected through total sampling. The instrument used was a self-regulation questionnaire adapted from the Self-Regulation Questionnaire–Academic (SRQ-A) with a four-point Likert scale. Data were analyzed through normality testing, homogeneity testing, and hypothesis testing using the Independent Sample T-Test with SPSS Statistics 19. The results showed that the control class obtained a mean self-regulation score of 55.92 (moderate category) with a mean post-test score of 69.79, while the experimental class obtained a mean self-regulation score of 77.00 (high category) with a mean post-test score of 83.65, reflecting a difference of 21.08 points in self-regulation between the two classes. Hypothesis testing yielded a Sig. (2-tailed) value of 0.000 < 0.05, leading to the rejection of H₀ and the acceptance of Hₐ. Therefore, there is a significant effect of implementing the ABC method assisted by Nearpod on strengthening the self-regulation of students at SDN 159 Palembang.